Pengaruh Burnout Digital dan Kelelahan Emosional Terhadap Kinerja Karyawan di Era Digital: Studi Pada BCA KCP Pringsewu - Bernadetha Elen Pratiwi; Defrizal Defrizal (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Digital transformation in the banking sector has increased the intensity of technology use in employee work activities. This condition has the potential to lead to digital burnout and emotional exhaustion, which impact employee performance. This study aims to analyze the influence of digital burnout and emotional exhaustion on employee performance, both partially and simultaneously. The study used a quantitative approach with a survey method of 20 employees of Bank BCA Pringsewu Branch Office selected using purposive sampling. Data analysis was performed using multiple linear regression. The results showed that digital burnout had a negative and significant effect on employee performance (β = -0.221; p < 0.05), emotional exhaustion had a negative and significant effect on employee performance (β = -0.954; p < 0.05), and both simultaneously had a significant effect on employee performance (F = 159.318; p < 0.05) with an Adjusted R² value of 0.943. These findings confirm that managing digital work pressure and employee emotional state are key factors in improving performance in the digital era.